University of higher education institutions in some parks on the need to organize the structures (Journal of Economic Research & Business Administration, 2015)
The universities of science and technology parks structures designed to study the needs of the organization. Technopark The main objective of the scientific and technical complex territorial and small creation of favorable conditions for effective functioning of business firms. These higher education institutions, research centers, formed at the laboratories. It is composed of: zerttewortalıqtarı incubator, innovative qortalıqtar marketing. come b.ortalıqtar. The industrial park for innovative enterprises in terms of accounting, auditing, consulting and marketing services will be offered.